Distorsi dalam Transisi Demokrasi di Indonesia - Soebagio, Soebagio (UI Scholars Hub, 2009)
Reformation which shifts democratization of the state gave constructive energy for Indonesian to reconstruct its democratic state. Therefore, reformation which became the democratic transition to democratic consolidation, is a phase toward substancial democratic state who prospers the people in politics, social & economics. In fact, the democratic transition is not always smooth; many distortions disturbing the democratic consolidation toward the realization of the democratic state appear.